Use of "tilapia" as a therapeutic agent in oral mucosal burns: An unprecedented proposal - Areeba Shahid; Shivakumar Channaiah Ganiga; Sahana Shivakumar (Wolters Kluwer Medknow Publications, 2021)
Water bodies purvey plenty of natural resources that are utilized to manufacture materials or are employed as novel medicines in medical and dental practice. Among sponges, corals, fishes, and other marine life forms, one promising source is the "tilapia fish." It is principally farmed for the utilization and construction of therapeutic biomaterials. As oral physicians or dental practitioners, we grapple with many oral lesions and wounds in routine practice, "burns" being one of them. Tilapia skin and its collagen are being applied for dermatological burns. Since the branch of medicine encourages innovative ideas and research work in the treatment of challenging oral lesions, this article aims to communicate the idea of its usefulness in oral burns and alike lesions, making tilapia a neoteric healing agent, keeping in mind the remarkable biological properties it possesses.